Extended thoracic endovascular aortic repair for residual aortic dissection after type A aortic dissection repair. (December 2021) - Iida, Yasunori; Hachiya, Takashi; Asano, Ryota; Inoue, Shinya; Fujii, Susumu; Sawa, Shigeharu; Shimizu, Hideyuki
Objective: We investigated the outcomes of extended coverage of the descending thoracic aorta by thoracic endovascular aortic repair (TEVAR) for residual chronic type B aortic dissection after type A aortic dissection (TAAD) repair. Methods: From November 2015 to August 2020, 36 patients underwent extended TEVAR for residual intimal tear after TAAD repair. We specifically investigated the methods and outcomes of this procedure. Results: TEVAR consisted of isolated TEVARs ( n = 29), single-vessel debranching TEVAR (6), and two-vessel debranching TEVAR (1). The mean time from TAAD repair to TEVAR was 27 ± 33 months (2–86 months). The TEVAR devices used were Valiant (28 cases), GORETAG (4), Relay plus (2), and TX2 (2). Technical success of TEVAR was 100%. The distal ends of the stent grafts were T 8 (1 case), T 9 (5), T 10 (6), T 11 (9), and T 12 (15), with an average of T 11 ± 1. The average length of hospital stay after TEVAR was 9 ± 3 days (5–17 days). There were no surgical/hospital deaths or complications. The average postoperative follow-up period was 21 ± 15 months without death or reintervention. Conclusions: The short-term outcomes of extended TEVAR for residual chronic type B aortic dissection after TAAD repair were acceptable without perioperative SCI. Aggressive descending thoracic aorta coverage may prevent aortic events, and extended TEVAR may be a preemptive treatment for the downstream aorta. Mid- to long-term results should be clarified.